Can some help me rearrange the below to find g. Thanks V = 9.94 + 2.465/1.09 + 2.525/1.09squared + (2.525*g/1.09-g)/1.09squared V = 52 sorry about the word squared could not write on my device. Thanks ben
Follow Math Help Forum on Facebook and Google+
52 - 9.94- (2.465/1.09) - (2.525/1.09^2)= (2.525g/1.09-g)/1.09^2 1.09^2(52 - 9.94- (2.465/1.09) - (2.525/1.09^2))= (2.525g/1.09-g)=g(2.525/1.09 - 1) g=(1.09^2(52 - 9.94- (2.465/1.09) - (2.525/1.09^2)))/(2.525/1.09 - 1)=33.9986
Thanks. Far more obvious when you know how.
View Tag Cloud